Changes in Neutrophil Count After Antipsychotic Prescription Among a Retrospective Cohort of Patients With Benign Neutropenia. Issue 4 (August 2017) - Campion, Paul; Campion, Gabriel; Anbarasan, Deepti
Abstract: Background: There is a paucity of literature regarding the effect of antipsychotics on absolute neutrophil count (ANC) of patients with benign neutropenia (BN). We evaluated the change in ANC after atypical antipsychotic prescription (excluding clozapine) in a retrospective cohort of 22 patients with BN. Methods/Procedures: Records of all patients with BN who were prescribed antipsychotics and who had ANC measured before and during antipsychotic treatment were obtained from Bronx VA Medical Center between 2005 and 2015 (inclusive). Twenty-two patients met criteria for inclusion. Individual and group mean ANC were calculated before treatment and during treatment. A paired, two-tailed t test was performed on the group ANC means. Results: The group mean pretreatment ANC was 1.24 ± 0.220 K/cmm, and the mean ANC during the time of antipsychotic prescription increased to 1.40 ± 0.230 K/cmm, with a P value of 0.0045, t value of 3.18, degrees of freedom equal to 21, and 95% confidence interval of 1.30 to 1.49 K/cmm. Conclusions: There was a statistically significant increase in ANC among our cohort during the time of antipsychotic prescription. All BN patients who were prescribed antipsychotics maintained a stable neutrophil count, with none of the 22 patients with BN in this study developing agranulocytosis during treatment. Although this study is limited by a low patient count as well as other demographic factors, these findings provide initial evidence regarding the safety of prescribing atypical antipsychotics to BN patients. Further studies are needed to replicate these findings and assess for effects of individual medications.